(untitled) (Revista de Ciências Agroveterinárias, 2017)
The environment can be a limiting factor for development of Physalis species seedlings. Thus, the aim of this present study was to evaluate the initial development of Physalis species when subjected to cultivation environments. The experimental design was a randomized block design, factorial 3 x 3 (three Physalis species being Physalis peruviana, P. angulata and P. pubescens x three environments, greenhouse - GRE, plastic cover with 150 micron; shading - PLS, with 75% permeability and light - SHD, full sun, in a fully open - FOP), with four repetitions, conducted between February and May/2012, at the Station of Horticulture and Biological Control “Mário César Lopes”, University of Paraná State, Brazil. During the experiment, the emergence speed rate of seedlings was monitored in the initial 30 days. At 76 days after the sowing, leaf area, dry biomass of leaves, stems and roots, as well as the number leaves, plant height and stem diameter were evaluated. The SHD environment provides higher percentage of emergence of Physalis species seedlings studied. GRE and SHD environments were similar to the early Physalis development and can be used in the production of these species seedlings. Is not advisable in the initial development of Physalis seedlings.